The Potential of Moringa Leaf Extract to Prevent Aging Targeted Cellular Senescence - Sri Andriyani; Rujitoningtyas, Karimatussholikah; Wigati, Hilmi U.; Amalina, Nur Dina (International Journal of Cell and Biomedical Science, 2022)
High exposure to ultraviolet light and chemicals causes cell senescence due to the overproduction of reactive oxygen species (ROS). Cell senescence is known as one of the causes of degenerative diseases. Reducing ROS levels using antioxidant compounds can overcome cell senescence. This study aimed to evaluate the potential of Moringa leaf extract (EDK) as an anti-aging agent and predict the molecular mechanisms underlying its activity. EDK active compounds were identified through qualitative phytochemical screening, a cytotoxic assay was evaluate using MTT assay, ROS level calculate under DCFDA flow cytometry assay, and cell senescence analyze using SA-β-galactosidase assay. The molecular mechanism that plays an important role in senescence was analyzed through bioinformatics studies and molecular docking in silico to investigate the interaction strength of the active compound EDK with the target protein. The results showed that the EDK ethanol extract contained flavonoid, phenolic, alkaloid, saponin, and steroid compounds. This extract did not give any cytotoxic effect on NIH3T3 cells, as evidenced by the IC50 value of 420μg/mL. EDK concentrations of ¼IC50 (105μg/mL) and ½IC50 (210μg/mL) significantly reduced ROS level in dose-dependent manner in the NIH3T3 cell population with high oxidative stress induced by Doxorubicin 10nM (Dox). The percentage of senescence cells also decreased due to EDK 210μg/mL administration up to 47.60% compared to the positive aging control Dox 10nM (78.90%). Bioinformatics studies found that p21 and TP53 proteins were most directly affected by EDK active compounds in the senescence pathway. The quercetin compound in EDK has the most robust interaction strength against p21 and TP53 proteins compared to ligands. In conclusion, it can be concluded that the active compound EDK can suppress intracellular ROS levels and compete with p21 and TP53 proteins in preventing cell senescence.